So Many Faces, Phases, and Facets, Sickness Behavior Beyond Disciplines - Konsman, Jan Pieter (Frontiers in Psychiatry, 2021)
Animals, including human beings, modify their behavior when they fall sick. Interestingly, sociology, biology and psychology have at different times in their history developed constructs of illness or sickness behavior. The aims of the present paper are to consider sickness behavior in humans and other animals and to evaluate to what extent the notions of sickness behavior would allow for interdisciplinary research. After distinguishing disease, illness and sickness, the case will be made that illness behavior and sickness behavior can be considered heuristically as synonyms given the existence of some fluidity between the notion of illness and sickness. Based on this, different faces, phases and facets of sickness behavior will be presented before addressing the question of how integration of constructs of sickness behaviors would be possible across biology, medicine, psychology and sociology. It is concluded that interdisciplinary research on sickness behavior between biology, psychology and sociology is possible and called with regard to constructs, methods and explanations, while keeping in mind differences in perspectives, for example between acute and chronic sickness behavior.